PEMBELAJARAN INTERAKTIF MOBILE LEARNING PADA MATA KULIAH PENDIDIKAN KEWARGANEGARAAN - Abdulah Abdulah (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
This research is motivated by problems that occur in the lecture process where students do not understand the explanations in textbooks, because they only explain theoretically without any learning media that makes it easier for students to understand and study the material in citizenship courses, development of interactive media mobile learning in citizenship education courses. This study aims to determine the effectiveness of mobile learning interactive media in citizenship education courses. This research uses a literature study that examines 7 journals that are relevant to the author's research. The type of data used is secondary data, namely data obtained indirectly. The data needed in this research is taken from documents related to research. Data collection techniques are carried out by reviewing and analyzing books and journals with rules related to mobile learning interactive media. The data analysis technique used is qualitative analysis. The results of this study indicate that the development of interactive mobile learning media can have an influence on student learning outcomes. Based on the results of data analysis using literature study research methods in 7 journals that were reviewed regarding the development of interactive mobile learning media, the results obtained were the results of the study showed that the development of interactive mobile learning media had an effect on student learning outcomes as seen from the results of the study of 4 quantitative research journals. and an increase in student learning outcomes based on the results of the study of 3 journals with classroom action research methods.